2012
DOI: 10.7314/apjcp.2012.13.6.2949
|View full text |Cite
|
Sign up to set email alerts
|

The GSTP1 Ile105Val Polymorphism is not Associated with Susceptibility to Colorectal Cancer

Abstract: The glutathione S transferase (GST) family is a major part of cellular defense mechanisms against endogenous and exogenous substances, many of which have carcinogenic potential. Alteration in the expression level or structure of the glutathione-S-transferase (GST) enzymes may lead to inadequate detoxification of potential carcinogens and consequently contribute to cancer development. A member of the glutathione-S-transferase (GST) family, GSTP1, is an attractive candidate for involvement in susceptibility to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 35 publications
1
8
0
1
Order By: Relevance
“…Another study from Jordan by Khabaz MN [71] revealed no statistically significant differences between GSTP1 genotypes and CRC risk.…”
Section: Gsts and Colorectal Cancermentioning
confidence: 99%
“…Another study from Jordan by Khabaz MN [71] revealed no statistically significant differences between GSTP1 genotypes and CRC risk.…”
Section: Gsts and Colorectal Cancermentioning
confidence: 99%
“…[15], and Khabaz [10]. These researchers concur that GSTP1 gene polymorphism does not exert any effect on the risk of contracting colorectal cancer.…”
Section: Importance Of Gst Gene Polymorphism In the Development Of Camentioning
confidence: 84%
“…These researchers concur that GSTP1 gene polymorphism does not exert any effect on the risk of contracting colorectal cancer. In the study by Khabaz, after analysing genotypes of 90 CRC tissue specimens and 56 specimens of healthy tissues of the large intestine, no statistically significant differences were observed between GSTP1 genotypes [10]. …”
Section: Importance Of Gst Gene Polymorphism In the Development Of Camentioning
confidence: 99%
“…In Saudi Arabia, few are the studies dealing with gene polymorphism and the susceptibility to CRC. No association could be detected between the susceptibility to CRC and resistin promoter C-180G genotype (Al-Harithy and Al-Ghafari, 2010), PARP-1 Val762Ala (Alshammari et al, 2014), GSTP1 Ile105Val (Khabaz, 2012) and autozygosity (Siraj et al, 2012). On the other hand, MMP-2C-qa306T ANP (Saeed et al, 2013 a), PARP1 Lys933Asn and Parp-1 Lys945Asn (Alshammari et al, 2014), rs 961253 Lys25Arg (Khan et al, 2014), CYP1A1, CYP2E1 and GSTM1 (Saeed et al, 2013b) were significantly associated withCRC.…”
Section: Discussionmentioning
confidence: 99%
“…According to the latest report of the National Cancer Registry (Al-Eid et al, 2011), CRC is the first most common cancer among Saudi males (12.9%) and the third among the Saudi females (9.4%), being the second most common malignancy among Saudis for all ages (10.3%). Sporadic CRC is a typical multifactorial disease, arising from environmental exposures (air pollution, dietary carcinogens, cigarette smoke), susceptibility genes and the interaction between genotypes and environments (Khabaz, 2012 andHezova et al, 2012)). Exposure to polycyclic aromatic hydrocarbons (PAHs) and heterocyclic amines (HCAs) have long been suspected to play a prominent role in CRC aetiology (Al-Saleh et al, 2008).…”
Section: Introductionmentioning
confidence: 99%